Exploring the Content, Function and Dimension of Religiosity in the Stories of the Alang Ghosts and Dapow Ghosts of the Bengkalis Malay Community - Roziah, Roziah; Sudirman Shomary; Hermaliza; Resy Oktadela; Nurhidayah; Nurul Huda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to explore the content, function, and dimensions of religiosity in these stories. Alang of Ghost And Ghost of Dapow who live in the Bengkalis Malay community. The study used a qualitative-descriptive approach with a cultural hermeneutics method. Data were obtained through field observations, in-depth interviews with traditional leaders and local communities, and documentation of oral stories. Analysis was carried out through narrative analysis, social function analysis using Malinowski's functionalism approach, and interpretation of religiosity based on the theory of dimensions of religiosity, especially Fetzer's concept. The results show that the content of ghost stories represents the daily life of the Bengkalis Malay community, which is centered on family, home, and the domestic environment. Ghost of Alang It functions as a means of educating children to be disciplined, obedient to their parents, and maintain good health through the habit of sleeping on time. Ghost of Dapow function to instill the values ​​of cleanliness, neatness, hard work, and the belief that sustenance comes from God and is influenced by human behavior. Socially, ghost stories function as a tool of social control, a medium for moral and religious education, and a means of passing down cultural values ​​from generation to generation. The religiosity dimension is strongly reflected through the assertion that supernatural beings are not omnipotent and are subject to the will of Allah SWT, and that prayer, verses of the Quran, and religious practices are the main means of spiritual protection.